2001
DOI: 10.1128/jcm.39.10.3736-3739.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Rifampin-Resistant Isolates of Mycobacterium tuberculosis from Hungary by DNA Sequencing and the Line Probe Assay

Abstract: Two regions of rpoB associated with rifampin resistance were sequenced in 29 rifampin-resistant (determined by the proportion method) isolates of Mycobacterium tuberculosis obtained from patients from three counties in Hungary. Of the 29 resistant strains, 27 had a mutation in either the 81-bp region (26 strains) or the N-terminal region (1 strain), while the other 2 strains had no mutations in either region. The locations and frequencies of the mutations differed from those previously reported. The most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
68
2
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 26 publications
11
68
2
2
Order By: Relevance
“…However, in our study sensitivity of the MTBDRplus assay measured for resistance to RIF was lower than those reported. Our results confirmed that the distribution can differ in some settings [15]. Although the prevalence of false-resistant and false-susceptible results seems to be infrequent, some authors have discussed the relevance of mutations in codon 533 to RMP resistance [16].…”
Section: Discussionsupporting
confidence: 85%
“…However, in our study sensitivity of the MTBDRplus assay measured for resistance to RIF was lower than those reported. Our results confirmed that the distribution can differ in some settings [15]. Although the prevalence of false-resistant and false-susceptible results seems to be infrequent, some authors have discussed the relevance of mutations in codon 533 to RMP resistance [16].…”
Section: Discussionsupporting
confidence: 85%
“…The most frequent mutation (41%) occurred at codon position 531. Although frequencies of particular mutations in RIF-resistant M. tuberculosis isolates may differ in different geographic areas, 4 generally the most frequent codon involved is also 531. 15,37,50 In contrast, resistance to INH was associated with a variety of mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Another result is that the correlation between the DST result and mutation in the genes associated with resistance to INH and RIF failed. Discrepancies in molecular detection related to phenotypic results have been previously documented, including those in Brazilian clinical strains (14,15). Mutation in these strains may have occurred in a different region than that of the target gene or perhaps there were other resistance mechanisms involved.…”
Section: Patient Follow-up Results and Discussionmentioning
confidence: 99%